PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA MELALUI DISIPLINDAN SEMANGAT KERJA KARYAWAN PADA SD MUHAMMADIYAH DI KABUPATEN JEMBER - Muhammad Rapita Kun Panuluh; Andi Sularso; Purnamie Titisari (RELASI : JURNAL EKONOMI, 2015)
This research aims to analyze and understand and prove empirically influence directly and indirectly working environment and compensation to job satisfaction employees through work discipline and working spirit at SD Muhammadiyah in Jember Regency. This research classified as exsplanatory reseach and confirmatory research at once with loading technique samples proportional sampling. Data acquisition will be done with questionnaires distribution directly and indirectly from respondents the teachers and school at Muhammadiyah in Jember Regency. Data that was recieved by processed by using analysis of Strtuctural Equation Model (SEM) with IBM SPSS AMOS 20 software.